1999
DOI: 10.1021/jp992263p
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the B̃+ State of the Chlorobenzene Cation Using Photoinduced Rydberg Ionization (PIRI) Spectroscopy

Abstract: The photoinduced Rydberg ionization (PIRI) spectra of the B̃+ state of the chlorobenzene cation were recorded via the origin, 6b, and 16a16b vibrations of the cation ground state (X̃+). The resonance-enhanced multi photon dissociation spectroscopy (REMPD) spectrum of the B̃+←X̃+ transition of the chlorobenzene cation was also obtained. To date it has been thought that B̃+←X̃+ is an electronically forbidden transition (C 2 v symmetry), taking place from the 2B1 ground state to a 2B2 excited state. The ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Our assignment of the B state of the C 6 H 5 Cl + ion to 1 2 B 2 (and assignment of the C state to 2 2 B 1 ) is in line with the assignment presented in all the published papers concerning excited states of the C 6 H 5 Cl + ion, except the paper of Anand et al [6]. In 1999 Anand et al [6] suggested assignment of the B state of C 6 H 5 Cl + to 2 B 1 based on their analyses on the vibrationally resolved PIRI spectra.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Our assignment of the B state of the C 6 H 5 Cl + ion to 1 2 B 2 (and assignment of the C state to 2 2 B 1 ) is in line with the assignment presented in all the published papers concerning excited states of the C 6 H 5 Cl + ion, except the paper of Anand et al [6]. In 1999 Anand et al [6] suggested assignment of the B state of C 6 H 5 Cl + to 2 B 1 based on their analyses on the vibrationally resolved PIRI spectra.…”
Section: Resultssupporting
confidence: 89%
“…In 1999 Anand et al [6] suggested assignment of the B state of C 6 H 5 Cl + to 2 B 1 based on their analyses on the vibrationally resolved PIRI spectra. However, 3 years later Kwon et al [8] again assigned the B state of C 6 H 5 Cl + to 2 B 2 based on their analyses on the vibrational spectra measured by mass-analyzed threshold ionization (MATI), and in their paper [8] they argued that in the PIRI experiments the C 6 H 5 Cl neutral prepared in a Rydberg state correlating with the cation ground state by two-photon absorption had been further excited and autoionzation or fragmentation in the B or higher electronic states had been observed, and in contrast the one-photo MATI technique did not suffer from the complication related to multiphoton absorption.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations